(3EOGQI GdEfJGL hGdYedjGJ (B/s - (3eGVj, eMeO Jhajbs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s)
(3jJfGhd gPG GdcJGH GOGQI GdYedjGJ GdEfJGLjI hbQGQ ehbY GdeTQhY hGdJQJjH GdOGNdj hcPG JNWjW hJUeje GdEfJGL hQbGHI GdLhOIs
Keywords: (3EOGQI GdEfJGL hGdYedjGJs; (3GdEfJGLjIs